2018
DOI: 10.1038/s41598-018-25695-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant mutations in the ABCG2 transporter uncovered by genetic analysis linked to erythrocyte membrane protein expression

Abstract: The ABCG2 membrane protein is a key xeno- and endobiotic transporter, modulating the absorption and metabolism of pharmacological agents and causing multidrug resistance in cancer. ABCG2 is also involved in uric acid elimination and its impaired function is causative in gout. Analysis of ABCG2 expression in the erythrocyte membranes of healthy volunteers and gout patients showed an enrichment of lower expression levels in the patients. By genetic screening based on protein expression, we found a relatively fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 60 publications
1
23
0
2
Order By: Relevance
“…In our recent work, we found a new missense variant, ABCG2-M71V, which resulted in about 50% reduction in the expression of the ABCG2 protein in the erythrocyte membrane of heterozygous carriers [21]. This mutation was found to be relatively frequent in a heterozygous form 1 3 (about 1%) in Europe, and we could demonstrate a major effect of this mutation on the expression and function of the ABCG2 protein.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…In our recent work, we found a new missense variant, ABCG2-M71V, which resulted in about 50% reduction in the expression of the ABCG2 protein in the erythrocyte membrane of heterozygous carriers [21]. This mutation was found to be relatively frequent in a heterozygous form 1 3 (about 1%) in Europe, and we could demonstrate a major effect of this mutation on the expression and function of the ABCG2 protein.…”
Section: Introductionmentioning
confidence: 56%
“…Previous studies have shown that the expression of the frequent ABCG2-Q141K variant is altered at several levels-reduced mRNA maturation, protein folding, membrane trafficking, and increased degradation of this protein have been suggested [24][25][26][27]. For the M71V variant our group demonstrated a reduced folding and trafficking in mammalian cells [21], while the partially defective F373C and T153M variants have not been studied as yet at the cellular level.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A vesén keresztül történő csökkent húgysavkiválasztás hátterében a proximalis tubularis epithelsejtek uráttranszporter fehérjéi, illetve az ezen proteineket kódoló génekben bekövetkező polimorfizmusok (singlenucleotide polymorphism, SNP) állnak. A teljes genomra vonatkozó genomvizsgálatok és funkcionális elemzések alapján ezek az SNP-k vagy a húgysavszekréció gátlása (például ABCG2, NPT1, NPT4 fehérjék), vagy a tubularis reabszorpció fokozása (például OAT4, URAT1, GLUT9) révén vezethetnek hyperuricaemiához és köszvényhez [1,19,20]. Ebben a vonatkozásban a közelmúltban hazai kutatók is végeztek vizsgálatokat [19].…”
Section: Az Uráttranszporterek Genetikai Háttereunclassified
“…A teljes genomra vonatkozó genomvizsgálatok és funkcionális elemzések alapján ezek az SNP-k vagy a húgysavszekréció gátlása (például ABCG2, NPT1, NPT4 fehérjék), vagy a tubularis reabszorpció fokozása (például OAT4, URAT1, GLUT9) révén vezethetnek hyperuricaemiához és köszvényhez [1,19,20]. Ebben a vonatkozásban a közelmúltban hazai kutatók is végeztek vizsgálatokat [19]. A húgysav-reabszorpcióban szerepet játszó transzporterek (például lezinurad, arhalofenát) gátlószerei fejlesztés alatt, bevezetés előtt állnak [21].…”
Section: Az Uráttranszporterek Genetikai Háttereunclassified